Genome-Wide Association Analysis of Flavor Precursor Traits in Chengkou Mountain Chicken - Haiwei Wang; Yu Huang; Lingbin Liu; Xin Zhang; Donghang Deng; Zhen Wang; Guangliang Gao; Qigui Wang (Animals, 2025)
Chengkou mountain chicken, a Chinese indigenous breed, exhibits unique flavor characteristics. However, the genetic basis of its flavor precursor substances remains unexplored. We performed a genome-wide association study (GWAS) using low-coverage whole-genome sequencing (lcWGS) and genotype imputation to explore genetic markers linked to flavor precursors (nucleotides, amino acids, etc.) in Chengkou mountain chicken breast muscle. We identified 44 SNPs potentially or significantly associated with flavor precursor traits and localized 18 genes. Functional analysis revealed eight important candidate genes, including ZBTB20, RFX4, MAMLD1, SYN3, ABTB3, PRPF39, LRFN5, and DGCR14, which may play key roles in influencing flavor precursor substances. Moreover, two SNPs residing in the haplotype block (53,448,483 bp to 53,450,834 bp) on chromosome 1 were significantly associated with a di-unsaturated acyl chain (C20:2) residue and mapped to the ABTB3 gene. This study analyzes the composition of flavor precursor substances in the pectoralis major muscle of Chengkou mountain chicken. Moreover, the SNPs, haplotypes, and candidate genes identified in this study can be used to improve the accuracy of the marker-assisted selection of traits related to flavor precursor substances in the breast muscle of chicken. In addition, the candidate genes that are significantly associated with these traits will potentially lay the foundation for future genetic selection aimed at improving the flavor traits of chicken meat.